Developing a 4F model-based self-reflection tool for deep learning in upper elementary students - Nina Wirdiyana; Supianto Supianto; Jenny Indrastoeti; Siti Poerwanti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Self-reflection in elementary learning is often unstructured and lacks standardized tools aligned with deep learning principles. This study developed a self-reflection instrument based on the 4F model (fact, feeling, finding, future) using the 4D development framework (Define, Design, Develop, Disseminate). Data were collected through field studies, interviews, and observations. Instrument construction included content validation (Aiken’s V), construct validation (CFA), and reliability testing (Cronbach’s Alpha = 0.717). Findings showed most of the 227 students demonstrated “good” or “fair” self-reflection abilities. The instrument is valid, reliable, and supports teachers in evaluating students’ reflective thinking. The novelty lies in integrating the 4F model within a deep learning context for elementary education. Broader application and external validation are recommended for future research.